Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/pssc.201001159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing on 320 nm cathodoluminescence from hexagonal boron nitride powders

Abstract: The effect of annealing in various atmospheres (N2, H2, NH3 O2 and vacuum) on the 320 nm emission bands of hexagonal boron nitride (h‐BN) powders has been investigated by cathodoluminescence (CL). The CL intensity was decreased by annealing in the N2, H2and NH3 atmospheres at 1200 °C, with H2and NH3 having more effect than N2. On the other hand, the annealing in the O2 atmosphere increased the CL intensity remarkably at annealing temperatures higher than 800 °C. These results suggest that the oxygen located ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Also phonon-assisted luminescence at 320 nm could be used for flat-panel lamps and electron emitters [16]. Besides, as shown in our previous work [17] the luminescence around 400 nm shows gas sensing properties.…”
Section: Introductionmentioning
confidence: 95%
“…Also phonon-assisted luminescence at 320 nm could be used for flat-panel lamps and electron emitters [16]. Besides, as shown in our previous work [17] the luminescence around 400 nm shows gas sensing properties.…”
Section: Introductionmentioning
confidence: 95%
“…24,25 Besides, the Ref. 26 showed that annealing of an h-BN micropowder in an O2 atmosphere at a temperature of 900 °C for 2 h results in an increase in both the oxygen content from 0.25 to 0.40 wt. % and the intensity of cathodoluminescence in the 320 nm (3.9 eV) band by almost 4 times as compared to the initial sample.…”
mentioning
confidence: 99%
“…25,29) The possibility of an oxygen impurity as the origin of this emission has also been discussed on the basis of the luminescence property of the oxygen-annealed h-BN powders. 30,31) On the other hand, the origin of the latter emission band is not clear at present. The dependences of CL spectra and XRD patterns on the growth temperature for the samples grown at 20 kPa suggested that the broad emission at about 350 nm is correlated with the disordered BN.…”
Section: Resultsmentioning
confidence: 85%